Peningkatan Keterampilan Menulis Berita dengan Pendekatan Terpadu dan Media Gambar pada Siswa Kelas VIII SMP Negeri 1 Teras - Hartati, Sri (Jurnal Manajemen Pendidikan, 2015)
The purpose of the research is to increase news-writing skills by applying integrated approach   and  images  utilization.The   research  is  a  type  of  action  research   which  was conducted  in  3  cycles.  The  main  activities  of  the  research  were  done  in  4  steps:  action planning, action implementation,  observation,  and reflection. The research was conducted to classVIIIA on the second term year 2013/2014 of Negeri 1 Teras Junior High School located in Boyolali. The subjects particularly were members of class VIIIA, consisting 32 students in total  with  the  same  ratio  of  girls  and  boys.  The  research  uses  field  notes,  observation guidelines,  and news-writing  trials as a method  of collecting  data. Descriptive-Qualitative method  is used to analyse the development  of writing skills. Both the process and the final results  are analysed  for this  research.  There  are three  conducted  cycles.  The result  of the research  showed  that  integrated  approach  and  imagesutilization   successfully  increase  the news-writing  skills of the students both quantitatively  and qualitatively.  Initially, merely 7 of 32 students  or approximately  21.88%  of the students  pass  the  average  level  while  the classical  learning  mastering  is 70.83%.  After the first cycle has been done, the number  of students who pass the average level increased significantly  to 26 out of 32 or 81.25% while classical  learning  mastery  increases  to  77.89%.  As  a  result,  the  succeed  criteria  of  the research  has not been achieved  yet. The mean score of the students  on first cycle is 77.89. Classical learning mastery is 85.07% therefore the succeed criteria has been passed this time. The mean score of the students  on the second  cycle is 85.07  which  increases  significantly compared to that on the first cycle.